2016
DOI: 10.5051/jpis.2016.46.4.266
|View full text |Cite
|
Sign up to set email alerts
|

Risk indicators related to peri-implant disease: an observational retrospective cohort study

Abstract: PurposeThe aim of the present study was to retrospectively investigate the influence of potential risk indicators on the development of peri-implant disease.MethodsOverall, 103 patients referred for implant treatment from 2000 to 2012 were randomly enrolled. The study sample consisted of 421 conventional-length (>6 mm) non-turned titanium implants that were evaluated clinically and radiographically according to pre-established clinical and patient-related parameters by a single investigator. A non-parametric M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…A retrospective cohort study recently published by Poli et al indicated that patients’ age ≥65 years is significantly associated with peri‐implantitis, as elderly patients often have chronic systemic diseases …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective cohort study recently published by Poli et al indicated that patients’ age ≥65 years is significantly associated with peri‐implantitis, as elderly patients often have chronic systemic diseases …”
Section: Discussionmentioning
confidence: 99%
“…A recently published study by Poli et al stated that patients were at higher risk for peri‐implantitis when >6 months relapsed per recall appointment, which means irregular follow‐up examinations including prophylaxis measures when needed (OR 4.69; 95% CI 1.17‐18.79). This is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…() reported on both implant and subject characteristics but did not attempt to analyse their effects on the prevalence of peri‐implantitis. Only three studies (Frisch, Ziebolz, Vach & Ratka‐Kruger, ; Passoni et al., ; Poli, Beretta, Grossi & Maiorana, ) examined the effect of keratinized mucosa on peri‐implant disease. Ferreira et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous investigations have indicated that insufficient keratinized tissue predisposes individuals to peri‐implant disease (Poli, Beretta, Grossi, & Maiorana, ; Pranskunas, Poskevicius, Juodzbalys, Kubilius, & Jimbo, ). In the present investigation, while keratinized tissue <2 mm did emerge as a discriminant between health and disease, it did not have significant predictive power in the classification algorithm.…”
Section: Discussionmentioning
confidence: 99%